2017
DOI: 10.14814/phy2.13176
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐mediated inhibition of EGFR reduces phosphate excretion and induces hyperphosphatemia and mild hypomagnesemia in mice

Abstract: Monoclonal antibody therapies targeting the EGF receptor (EGFR) frequently result in hypomagnesemia in human patients. In contrast, EGFR tyrosine kinase inhibitors do not affect Mg2+ balance in patients and only have a mild effect on Mg2+ homeostasis in rodents at elevated doses. EGF has also been shown to affect phosphate (Pi) transport in rat and rabbit proximal convoluted tubules (PCT), but evidence from studies targeting EGFR and looking at Pi excretion in whole animals is still missing. Thus, the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, clinical studies demonstrated that patients receiving anti-epidermal growth factor receptor (EGFR) antibody therapy in trials for colorectal and other forms of cancer also J o u r n a l P r e -p r o o f demonstrate kidney magnesium wasting 29 . Previous studies showed when rodents were treated with an anti-EGFR monoclonal antibody (ME-1), they had mild, yet significantly decreased phosphate excretion, increased serum phosphate, as well as decreased serum magnesium 30 .…”
Section: Function Of Fgf23 After Blocking Egfr In Vitromentioning
confidence: 99%
“…Additionally, clinical studies demonstrated that patients receiving anti-epidermal growth factor receptor (EGFR) antibody therapy in trials for colorectal and other forms of cancer also J o u r n a l P r e -p r o o f demonstrate kidney magnesium wasting 29 . Previous studies showed when rodents were treated with an anti-EGFR monoclonal antibody (ME-1), they had mild, yet significantly decreased phosphate excretion, increased serum phosphate, as well as decreased serum magnesium 30 .…”
Section: Function Of Fgf23 After Blocking Egfr In Vitromentioning
confidence: 99%
“…We have previously shown that MEMO1-deficient cells are resistant to treatment with EGF [ 4 ] and FGF23 [ 2 ]. In the same line, antibody-mediated EGFR inhibition was recently shown to reduce renal phosphate excretion and concomitantly to decrease magnesemia in mice [ 29 ]. MEMO1 may thus be involved in the crosstalk between the two pathways.…”
Section: Discussionmentioning
confidence: 99%